Clinical Outcome in Male Patients With Detrusor Overactivity With Impaired Contractility - Shuo Liu; Lewis Chan; Vincent Tse (International Neurourology Journal, 2014)
PurposeTo review the clinical outcomes of patients with voiding dysfunction who have detrusor overactivity with impaired contractility (DOIC) diagnosed with urodynamic studies.MethodsUrodynamic reports from 2005 to 2009 were reviewed, and 54 male patients had findings consistent with DOIC. Patients with acontractile or neuropathic bladders were excluded. Clinical outcomes were obtained from patient records.ResultsOf 54 men, 8 presented with voiding symptoms, 17 had storage symptoms, and 29 had mixed symptoms. Twenty-two had a previous transurethral resection of the prostate. The median follow-up was 12 months. Four patients received no intervention. Two patients were taught intermittent self-catheterization. Five patients underwent surgery to reduce outlet resistance and all reported improvement. Forty-three patients were started on pharmacotherapy; symptomatic improvement was reported by 9 of 16 patients commenced on anticholinergics alone, 6 of 16 on alpha-blockers alone, and 4 of 5 treated with a combination of alpha-blockers and anticholinergics. Eleven patients experienced no difference on pharmacotherapy and 2 reported deterioration. One patient developed acute urinary retention (18 months after commencing treatment with alpha-blockers). No patient had urosepsis.ConclusionsAnticholinergics and alpha-blockers appear to be safe in patients with DOIC. The risk of urinary retention and sepsis is low. The majority of patients report symptomatic benefit from either drugs or surgical treatment.